CENTRAL OBESITY DETECTION AND WEIGHT MANAGEMENT - Gita Dwi Prasasty; Chairil Anwar; Desi Oktariana; Nia Savitri Tamzil; Evi Lusiana; Dwi Handayani (Conferences of Medical Sciences Dies Natalis, 2021)
Obesity is a multifactorial disease that occurs due to excess fat tissue that can interfere with health. It is estimated that obesity will reach more than 50% in developed countries. In Indonesia, the prevalence of obesity in people over 18 years old is 21.8%. Environment or diet is one of the causes of obesity. Community service activities were carried out on October 18, 2021, in Kuto Batu Village, Palembang, with the main target being community cadres with a minimum of 30 participants. Based on the pre-test results conducted on 32 participants, 60% already had a good knowledge of obesity and central obesity and weight management. However, unfortunately, more than half of the participants (65%) were overweight and even obese type 2, and 12% of participants were underweight, while the rest were normal. The results of the blood pressure examination showed that 62% of the participants had blood pressure greater than or equal to 130/80 mmHg. The data also showed that most of the overweight and obese participants had above-normal blood pressure. The same results in the participant's abdominal circumference as many as 62% had central obesity.